Unemployment in the Soviet Union: Evidence from the Soviet Interview Project - Gregory, Paul R.; Collier, Irwin L. (American Economic Review, 1988)
An unemployment rate for the urban population living in the European U.S.S.R. for the late 1970s is calculated from a survey of 2, 793 former Sovi et citizens residing in the United States. Patterns of unemployment i ncidence, frequency of multiple spells, and unemployment duration by demographic characteristics are compared with U.S. patterns. In contr ast, similar unemployment rates for Soviet men and women, and a posit ive relation between education and unemployment, are found. The Sovie t unemployment rate is low compared to Western rates for the 1970s, b ut has been matched by West Germany and Japan in high-employment year s. Copyright 1988 by American Economic Association.